Anti-scarring drug discovery: potential targets and therapeutic opportunities - Meiling Feng; Xiaotian Niu; Shan Wang; Liuxin Lu; Xilong Feng; Xiaoying Jiang; Wenchao Chen; Renren Bai (European Journal of Medicinal Chemistry Reports)
Scar formation is a ubiquitous pathological response during the skin wound healing process. While physical therapy can effectively mitigate scar development, it is often accompanied by issues such as poor patient compliance and a range of side effects. Consequently, there is an urgent clinical need for the discovery of effective anti-scarring drugs. However, this need has not been fully addressed to date. This review delves systematically and comprehensively into the characteristics of scars, the underlying mechanisms of their formation, and potential therapeutic targets. Additionally, it reviews drug repurposing efforts, natural products and small molecule compounds in the drug discovery stage with anti-scarring effects. The information presented herein will offer valuable insights and enlightenment for exploring potential targets and pathways, as well as viable lead compounds for the discovery and development of novel anti-scarring drugs.